Quality of Human Resources, Accounting Information Systems, Internal Control, and Accounting Policies as Determinants of Financial Statement Accountability - Durita Ardarani; Nila Sari; Ibnu Fajarudin; Emiliya Rahma Wati (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Accountability of local government financial statements is an important aspect in realizing transparency and good governance, so that the quality of information presented can be trusted by the public. Increasing this accountability requires qualified human resources, reliable accounting information systems, effective internal controls, and consistent accounting policies. This research aims to analyze the influence of human resource quality, accounting information systems, internal control, and accounting policies on the accountability of regional government financial reports. The research was conducted at the Regional Financial and Asset Management Agency (BPKAD) of Sidoarjo Regency, with an observation period from the first quarter to the third quarter of 2024. The study utilized a quantitative research method incorporating descriptive and associative strategies. Questionnaires were administered to staff responsible for financial report compilation to gather data. Multiple linear regression was employed for data analysis to assess the impact of various factors on financial report accountability. The discoveries revealed that the quality of human resources, accounting information systems, internal control, and accounting policies positively and substantially influence regional government financial report accountability. The evidence points to the fact that enhanced human resource quality, upgraded information systems, efficient internal control measures, and sound accounting policies lead to heightened accountability in regional government financial reporting.